2018
DOI: 10.1002/lt.25287
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Donor Warm Ischemia Time in Donation After Circulatory Death Liver Transplantation: Hypotension or Hypoxia?

Abstract: The aim of this study was to investigate the impact of hypoxia and hypotension during the agonal phase of donor warm ischemia time (DWIT) on hepatic ischemia/reperfusion injury (IRI) and complications in donation after circulatory death (DCD) liver transplantation. A retrospective single-center study of 93 DCD liver transplants (Maastricht type III) was performed. DWIT was divided into 2 periods: the agonal phase (from withdrawal of treatment [WoT] until circulatory arrest) and the asystolic phase (circulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…Research has shown that an oxygen saturation of less than 80% should be considered as the start of the functional DWIT. 20 However, in LTs with DCD-V grafts, the donor oxygen saturation and blood pressure levels are often not measured. In the few cases in which these parameters were measured, it was done noninvasively to minimize harm to the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that an oxygen saturation of less than 80% should be considered as the start of the functional DWIT. 20 However, in LTs with DCD-V grafts, the donor oxygen saturation and blood pressure levels are often not measured. In the few cases in which these parameters were measured, it was done noninvasively to minimize harm to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary outcomes were the occurrence of early allograft dysfunction, hepatic artery thrombosis, and nonanastomotic biliary strictures within the first year after the LT. As described, the DWIT can be divided into an agonal phase and an asystolic phase. 20 In an LT with DCD-V graft, the agonal phase was defined as the time between administration of euthanatics (coma-inducing drug and nondepolarizing neuromuscular blocking agent) and circulatory arrest. In an LT with DCD-III graft, the agonal phase was defined as the period between withdrawal of life-supporting treatment and circulatory arrest.…”
Section: Primary and Secondary Outcomes And Definitionsmentioning
confidence: 99%
“…Hypoperfusion longer than 20 minutes following withdrawal of care correlates with LT failure . Kalisvaart et al showed that hypoxia was a better indicator for graft loss and suggested SpO 2 below 80% for onset of WIT.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have linked decreased oxygen during the agonal phase to poor outcomes for LT and KT . Specifically, a prolonged period with SpO 2 levels below 80% during the agonal phase is detrimental to graft quality and resulted in unsuccessful graft retrieval .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation